Bureaucratica - Khan, Saif R. (Islamabad, Pakistan : Rahman Publishers, 1992)
Witty articles on Pakistani bureaucratic system, previously published in the dailies, Muslim, Islamabad, and Pakistan times, Lahore, during 1979-1981.
Koleksi sumbangan Tun (Dr.) Ahmad Sarji Abdul Hamid.
Keywords: Wit and humor -- Pakistan; Bureaucracy -- Pakistan -- Humor